1991
DOI: 10.1254/jjp.55.391
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of the novel .ALPHA.-adrenoceptor antagonist KT-611(naftopidil).

Abstract: ABSTRACT-The pharmacological profile of a new alpha-adrenoceptor antagonist, , was studied in vitro. In the dog mesenteric and carotid arteries and in the rabbit, guinea pig and rat thoracic aortae, KT-611 competitively inhibited a 1-adrenoceptor-mediated contractions induced by noradrenaline with pA2 values ranging from 6.73 to 8.15. KT-611 also inhibited the postjunctional a2-adrenoceptor mediated contractions in the dog saphenous vein (pA2 = 6.77) or dog basilar artery. However, the responses mediated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Concordantly, naftopidil-induced increases in plasma catecholamines were not observed in the rat (54). Likewise, naftopidil (1 pM) did not relax KCLcontracted dog mesenteric arteries (41). Higher concentrations (10 pM) of naftopidil, however, caused relaxation of rat aortic strips precontracted with 40 mM KC1 (57), which could possibly be explained by blockade of voltage-dependent Ca2 + channels.…”
Section: Pharmacodynamicsmentioning
confidence: 91%
“…Concordantly, naftopidil-induced increases in plasma catecholamines were not observed in the rat (54). Likewise, naftopidil (1 pM) did not relax KCLcontracted dog mesenteric arteries (41). Higher concentrations (10 pM) of naftopidil, however, caused relaxation of rat aortic strips precontracted with 40 mM KC1 (57), which could possibly be explained by blockade of voltage-dependent Ca2 + channels.…”
Section: Pharmacodynamicsmentioning
confidence: 91%
“…Neither tamsulosin nor naftopidil is highly subtype-selective for ␣ 1A -ARs and ␣ 1D -ARs, respectively. However, naftopidil is an ␣ 1 -AR antagonist with weak antagonistic activity for ␣ 2 -AR [11] , leading to the hypothesis that ␣ 2 -AR antagonists may influence afferent pathways of the LUT and improve storage symptom. Although ␣ 2 -ARs are well researched in terms of the efferent pathways to the LUT [12][13][14][15][16] , the function of these receptors in the afferent system does not appear to have been studied.…”
Section: Effects Of ␣ -Blockers On Afferent Pathwaysmentioning
confidence: 99%
“…An in vivo study in dogs showed that the selectivity index (dose ratio required to produce a 50% inhibition of the prostatic pressure and mean blood pressure) was higher for naftopidil (3.76) than for tamsulosin (1.23) and prazosin (0.61) 7 . Naftopidil also has weak antagonistic activity to post‐junctional α 2 ‐adrenoceptors 8 …”
Section: Introductionmentioning
confidence: 99%